Partial Mechanical Unloading of the Heart Disrupts L-Type Calcium Channel and Beta-Adrenoceptor Signaling Microdomains - Wright, Peter T.; Sanchez-Alonso, Jose L.; Lucarelli, Carla; Alvarez-Laviada, Anita; Poulet, Claire E.; Bello, Sean O.; Faggian, Giuseppe; Terracciano, Cesare M.; Gorelik, Julia (Frontiers in Physiology, 2018)
Introduction We investigated the effect of partial mechanical unloading (PMU) of the heart on the physiology of calcium and beta-adrenoceptor-cAMP (βAR-cAMP) microdomains. Previous studies have investigated PMU using a model of heterotopic-heart and lung transplantation (HTHAL). These studies have demonstrated that PMU disrupts the structure of cardiomyocytes and calcium handling. We sought to understand these processes by studying L-Type Calcium Channel (LTCC) activity and sub-type-specific βAR-cAMP signalling within cardiomyocyte membrane microdomains. Method We utilized an 8-week model of HTHAL, whereby the hearts of syngeneic Lewis rats were transplanted into the abdomens of randomly assigned cage mates. A pronounced atrophy was observed in hearts after HTHAL. Cardiomyocytes were isolated via enzymatic perfusion. We utilized Förster Resonance Energy Transfer (FRET) based cAMP-biosensors and scanning ion conductance microscopy (SICM) based methodologies to study localisation of LTCC and βAR-cAMP signalling. Results β2AR-cAMP responses measured by FRET in the cardiomyocyte cytosol were reduced by PMU (Loaded 28.51±7.18% .vs Unloaded 10.84±3.27% N,n 4/10-13 mean±s.e.m *p<0.05). There was no effect of PMU on β2AR-cAMP signalling in RII_Protein Kinase A domains. β1AR-cAMP was unaffected by PMU in either microdomain. Consistent with this SICM/FRET analysis demonstrated that β2AR-cAMP was specifically reduced in t-tubules(TTs) after PMU (loaded TT 0.721±0.106% vs. loaded crest 0.104±0.062%, unloaded TT 0.112±0.072% vs. unloaded crest 0.219±0.084% N,n 5/6-9 mean±s.e.m **p<0.01, ***p<0.001 vs. loaded TT). By comparison β1AR-cAMP responses in either TT or sarcolemmal crests were unaffected by the PMU. LTCC occurrence and open probability (Po) were reduced by PMU (loaded TT Po 0.073±0.011% vs. loaded crest Po 0.027±0.006% N,n 5/18-26 mean±s.e.m *p<0.05) (unloaded TT 0.0350±0.003% vs. unloaded crest Po 0.025 N,n 5/20-30 mean±s.e.m NS #p<0.05 unloaded vs. loaded TT). We discovered that PMU had reduced the association between Caveolin-3, Junctophillin-2 and Cav1.2. Discussion PMU supresses’ β2AR-cAMP and LTCC activity. When activated, the signalling of β2AR-cAMP and LTCC become more far-reaching after PMU. We suggest that a situation of ‘suppression/decompartmentation’ is elicited by the loss of refined cardiomyocyte structure following PMU. As PMU is a component of modern device therapy for heart failure this study has clinical ramifications and raises important questions for regenerative medicine.